Supramolecular Hydrogen Bonded 3D Molecular Self Assembly Constructed from [(Co (nicotinamide)2(thiocyanate)2(H2O)2] Complex Showing Anti-ferromagnetic Character - Pandey, Deepanjali; S.Narvi, Shahid; Chaudhuri, Siddhartha (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
A new three dimensional hydrogen bonded cobalt frame work from [Co(nicotinamide)2(thiocyanate)2(H2O)2] was synthesized and characterized by X-ray diffraction, magnetism ,TGA and IR spectroscopy. The compound crystallizes in Triclinic space group P-1 with a = 7.5475(19), b = 8.054(2), c =8.932(2). Alpha=73.347(4), beta=70.067(4), gamma=66.559(4) with space group P-1 Z = 1, ’C14 H16 N6 Co O4 S2’, Mr =455.38, F(000) = 233 and Î¼(MoKÎ±) =0.71073 mm-1. The final R = 0.0497 and wR = 0.1461 for 4185 observed reflections with I > 2Ïƒ(I) and R = 0.0721 and wR = 0.1619 for all data. X-ray diffraction analyses revealed that Co(1) is linked by the nicotinamide ligands to form the ladder shape along the c axis, which is further extended into two-dimensional networks via the joint of Co(2) along the a axis. Moreover, these two dimensional motifs are interconnected by the thiocyanate S...H bridges to form a complicated 3-D polymeric framework. The magnetic susceptibility data at 1000Oe external field in the temperature range 2-300 K obeys the Curie-Weiss law, giving Î¸ = -24.12 K and C =2.43 thus indicating a dominant strong antiferromagnetic interaction and/or spin orbital coupling between the Co (II) ions.